Food and financial coping strategies during the monthly Supplemental Nutrition Assistance Program cycle - Kinsey, Eliza Whiteman (SSM Popul Health, 2019)
One in seven Americans participates in the Supplemental Nutrition Assistance Program (SNAP), making it the largest federally funded food assistance program. SNAP benefits are distributed once per month and both food spending and calorie consumption tend to decrease as time from benefit distribution increases. The monthly SNAP benefit cycle has serious implications for the health and financial stability of low-income families, a growing number of whom rely on SNAP as their sole source of income. Relatively little is known about the specific coping strategies households use to manage the SNAP cycle. The purpose of this study is to provide a critical exploration of the nature and timing of coping strategies for managing the SNAP cycle, including implications these coping mechanisms have for health and financial stability. This paper presents data from a prospective cohort study of mothers (n = 12) receiving SNAP benefits in Philadelphia between 2016 and 17. Both in-depth qualitative and survey methods were used. Participants reported on a variety of coping strategies they used to manage the SNAP cycle, including adjustments to shopping and eating patterns, mental accounting, emotional resilience, and social support. Instrumental social support was particularly vital in the final days of the benefit cycle, as were skipping meals and purchasing less expensive, energy-dense foods. Constant vigilance was required throughout the month to manage financial instability. The coping strategies for managing the SNAP cycle have short-term benefits, such as buffering against hunger and financial instability, however these survival strategies may have negative long-term repercussions for physical and financial health.